Diseño de hélices optimizadas para mejorar el sistema de empuje de un drone modelo T4. - Gabriel Sebastián, Inca Yajamín (2020)
The present project is focused on improving the thrust system of a T4 model drone through the design of an optimized and experimentally validated propeller, for which, the aerodynamic resistance induced by the generation of vortices in the tips of the propellers was analyzed and thus determine the optimal wing tip angle that allows reducing such resistance. The process begins with the selection of the NACA 6609 aerodynamic profile based on the aerodynamic analyses described in the NACA No. 824 and NACA No. 824 reports. This profile is used for the design of the APC 1555 propeller on which a total of eight different modifications were made in the wing tip angle also called "winglet"; after the design, the simulation of each modified propeller is carried out by means of the study of computerized fluids in ANSYS software. The results by the CFD for the propellers with angles of 60 and 45 degrees in the wing tip show a remarkable improvement in relation to the other designs, for this reason these propellers were selected for 3D printing with PLA material. The experimental validation was carried out at an altitude of 2600 m.a.s.l. using an RCbenchmark model 1520 test bench, a 400 KV GARTT ML4112 engine and a four-cell 14.8 VDC graphite battery with a capacity of 1300 mAh. The results obtained on the test bench for the 60 degree propeller show an average increase in efficiency of 9.49%, and for the 45 degree propeller they show an increase of 8.42% with respect to the original propeller.